European monetary integration and aggregate relative deprivation: The dull side of the shiny euro - Oded Stark; Julia Wlodarczyk (University of Tübingen, Faculty of Economics and Social Sciences, 2015)
Drawing on the premise that the integration of economies revises people's social space and their comparators, we quantify social stress by aggregate relative deprivation, ARD; we calculate the effect of monetary mergers on ARD; and we document the validity of the superadditivity property of ARD for successive adoptions of a common currency by European countries. One feature of monetary unification, which replaces diverse currencies with a common currency, is that it brings about a change in the comparison environment, expanding the reference space of individuals in a given country to encompass individuals from the joining countries. Overall, calculations regarding six enlargements of the Economic and Monetary Union between 1999 and 2011 reveal an increase of ARD on six occasions when we hold incomes constant, and on five when we take into consideration changes in incomes. In addition, we observe an uneven distribution of the costs and benefits from monetary integration among the participating countries when these costs and benefits are measured in terms of ARD.
Keywords: D31; D63; E42; E44; F33; P51; 330; Monetary integration; Aggregate relative deprivation; Superadditivity; Social stress